Development and Evaluation of Augmented Object Prototypes for Notifications in Collaborative Writing Environments - Brenes Carranza, José Antonio (2016)
In Ubiquitous Computing, augmented objects refer to those elements of the real world which have been provided with computational capabilities to meet a specific need. Meanwhile, Collaborative Writing Environments (CWE) allow groups of people to work together and increase the chances of success and share knowledge when they are working on shared documents. An extremely important aspect in CWEs is notification mechanisms as these are essential to provide users awareness about the collaborative work they are doing. In this paper, we describe a set of augmented objects created to support the notification in CWEs; these objects can improve the way in which the notifications are delivered to users, according to the writing strategy defined by the collaboration team.